Divergent Hydraulic Safety Strategies in Three Co-occurring Anacardiaceae Tree Species in a Chinese Savanna - Zhang, Shu-Bin; Zhang, Jiao-Lin; Cao, Kun-Fang (Frontiers in Plant Science, 2017)
Vulnerability segmentation, the condition under which plant leaves are more vulnerable to drought-induced cavitation than stems, may act as a “safety valve” to protect stems from hydraulic failure. Evergreen, winter-deciduous, and drought-deciduous tree species co-occur in tropical savannas, but there have been no direct studies on the role of vulnerability segmentation and stomatal regulation in maintaining hydraulic safety in trees with these three leaf phenologies. To this end, we selected three Anacardiaceae tree species co-occurring in a Chinese savanna, evergreen Pistacia weinmanniifolia, drought-deciduous Terminthia paniculata, and winter-deciduous Lannea coromandelica, to study inter-species differentiation in leaf and stem hydraulic safety. We found that the two deciduous species had significantly higher sapwood-specific hydraulic conductivity and leaf-specific hydraulic conductivity than the evergreen species. Moreover, two deciduous species were more vulnerable to stem cavitation than the evergreen species, although both drought-deciduous species and evergreen species had drought-resistance leaves. The evergreen species maintained a wide hydraulic safety margin (HSM) in stems and leaves; which was achieved by embolism resistance of both stems and leaves and isohydric stomatal control. Both deciduous species had limited HSMs in stems and leaves, being isohydric in the winter-deciduous species and anisohydric in drought-deciduous species. The difference in water potential at 50% loss of hydraulic conductivity between the stems and the terminal leaves (P50leaf-stem) was positive in P. weinmanniifolia and L. coromandelica, whereas, T. paniculata exhibited a lack of vulnerability segmentation. In addition, differences in hydraulic architecture were found to be closely related to other structural traits, i.e., leaf mass per area, wood density, and sapwood anatomy. Overall, the winter-deciduous species exhibits a drought-avoidance strategy that maintains the hydraulic safety of the more carbon-costly stems by sacrificing cheaper and more vulnerable leaves, while the evergreen species exhibits a hydraulic strategy of drought tolerance with strong stomatal regulation. In contrast, the drought-deciduous species lacks vulnerability segmentation and sheds leaves at the expense of top shoots during peak drought. This study demonstrates that even sympatric tree species that differ in leaf phenology can exhibit divergent adaptive hydraulic safety strategies.